2015
DOI: 10.1111/1460-6984.12135
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of treatment targeting syntax production in people with Broca's‐type aphasia: evidence from psycholinguistic assessment tasks and everyday conversation

Abstract: Improvement in language production in constrained assessment tasks may not impact on everyday conversations. Implications for further research are discussed, e.g. the need for bridging interventions between constrained and unconstrained contexts of language production. Clinical implications include the potential to streamline therapy planning and delivery by making use of rich, hybrid therapies to treat individuals with similar symptom profiles but with a range of underlying deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…There was no significant change in the number of facilitators for the group (minimal numerical increase from 33.7 to 35.7 on average in 5 min of conversation). This is a new finding and it stands alone as, while there are some well controlled case studies in the literature (Carragher et al, 2015), there is no research examining change at a group level in conversation behaviors after an intervention with a direct focus on conversation. The differing findings for the experimentally controlled case series are important in highlighting the variability between dyads making up the group.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There was no significant change in the number of facilitators for the group (minimal numerical increase from 33.7 to 35.7 on average in 5 min of conversation). This is a new finding and it stands alone as, while there are some well controlled case studies in the literature (Carragher et al, 2015), there is no research examining change at a group level in conversation behaviors after an intervention with a direct focus on conversation. The differing findings for the experimentally controlled case series are important in highlighting the variability between dyads making up the group.…”
Section: Discussionmentioning
confidence: 97%
“…Whilst there is evidence that grammatical ability in the clinical setting can be improved in this way, it has proved hard to detect carryover to everyday conversation; indeed there are few studies where this is explicitly evaluated. It may be that generalization occurs but much research has failed to capture it (Carragher et al, 2015). In the field of anomia therapy, there is evidence that work on retrieving single words can influence connected speech tasks and conversation (Conroy et al, 2009; Best et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Aphasia classification was based on clinical consensus, grammatically impoverished output on picture description tasks, and performance on standardised language assessments (Table 1; for more details see Carragher et al, 2013, p. 852;Beeke, Maxim, Best, & Cooper, 2011, p. 228). Dyads took part in intervention studies (dyads 1-8: Carragher et al, 2013;Carragher, Sage, & Conroy, 2015;dyad 9: Best et al, 2016) and recorded weekly conversations prior to, during and after intervention. Analysis is based on pre-therapy recordings only and the nature of interventions is not relevant to the current study.…”
Section: Participantsmentioning
confidence: 99%
“…A 2002 study (48) reported that gains in generalization are limited, as observed in some of the selected studies (24,36,37,39,42) . However, findings from some studies of this review have shown that participants treated within this approach had gains in generalization to untrained items (13,15,19,28,32) .…”
Section: Discussionmentioning
confidence: 82%
“…M o s t s t u d i e s u s e d l e x i c a l -p h o n o l o g i c a l stimuli (16)(17)(18)20,22,23,(26)(27)(28)(29)33,35,40,41,43,44) and semantic stimuli (13,15,25,30,31,36,38,39,42) , and some studies used verbs (19,21,24,32,37) . Another study also reported picture naming as the main task used during word retrieval treatment.…”
Section: Discussionmentioning
confidence: 99%